FORMULASI SEDIAAN SPRAY GEL EKSTRAK DAUN BANDOTAN (Ageratum conyzoides.L) SEBAGAI ANTINYAMUK - Mangalik, Anastasia Reni; Helmidanora, Rusdiati; Sa'adah, Hayatus (Jurnal Riset Kefarmasian Indonesia, 2023)
There are many types of mosquitoes that cause disease in humans, one of which is the Anopheles mosquito that spreads malaria. Bandotan plants are used to treat colic, flu, fever, antidiarrheal, diarrhoea. The purpose of this study was to determine the concentration of bandotan (Ageratum conyzoides.L) leaf extract that provides the best physical properties and anti-mosquito activity in spray gel preparations. The research method conducted was experimental. The object studied was the formulation of bandotan leaf preparation as an antinyamite. The research stages include plant determination, sample collection, simplisia preparation, extraction using maceration method with 70% ethanol solvent, identification of secondary metabolite compounds, preparation of spray gel formula, and preparation evaluation. Bandotan leaf extract was formulated into anti-mosquito spray gel preparations with concentration variants of 10%, 15%, 20%, and using positive control of X brand anti-mosquito spray as a comparison. The preparation testing included organoleptic test, homogeneity test, pH test, viscosity test, and mosquito repellency test. The results of data collection were analysed statistically. A good preparation formula is found in the negative control formula because it has a stable consistency and pH. The results showed that the ethanol extract of bandotan leaves was not significantly different from the organoleptic test, homogeneity test, viscosity test, and pH test. The greatest mosquito repellency was at a concentration of 20% which was 66.33%, at concentrations of 10% and 15% had an average anti-mosquito activity of 22.83% and 57.83% respectively for the positive control with brand X of 99.30%.